Nikah Batin dalam Serial Bidaah: Perspektif Hukum Islam dan Perlindungan Perempuan - Nauroh, Nauroh; Subhi, Muhamad Rifa’i (Jurnal ini dipublikasikan oleh Pusat Penelitian dan Pengabdian Publikasi (P3M) STAI Nahdlatul Watan Samawa-licensed under a Creative Commons Attribution-ShareAlike 4.0 International License., 2025)
In this study entitled inner marriage in the bidaah series, it describes the Malaysian drama series Bidaah seen from the perspective of Islamic law and its implications for the protection of women. The main issues to be discussed are the justification of inner marriage according to Islamic law and the social and legal impacts that arise, especially exploitation and sexual violence against women. The purpose of this study is to assess how the practice of inner marriage is in accordance with the provisions of Islamic law so that it can analyze how this practice can affect the protection of women. By using a qualitative approach with a literature study method related to Islamic marriage law and inner marriage cases that exist in society. The results of the study show that the practice of inner marriage in the series is contrary to the legal requirements of an Islamic marriage because it does not meet the pillars and requirements such as the presence of a guardian, witnesses and an official contract. In addition, this practice is manipulative and there is sexual violence against women due to forced abortion and social stigma. This study also found differences between the practice of inner marriage in the series and the tradition of legitimate inner marriage in the tarekat in several regions. So this study emphasizes the need for the role of religious instructors to educate to protect women from the misuse of inner marriage which will be detrimental.